RNA and mRNA Nitration as a Novel Metabolic Link in Potato Immune Response to Phytophthora infestans - Izbiańska, Karolina; Floryszak-Wieczorek, Jolanta; Gajewska, Joanna; Meller, Barbara; Kuźnicki, Daniel; Arasimowicz-Jelonek, Magdalena (Frontiers in Plant Science, 2018)
Peroxynitrite (ONOO¯) exhibits a well-documented nitration activity in relation to proteins and lipids; however, the interaction of ONOO¯ with nucleic acids remains unknown in plants. The study uncovers RNA and mRNA nitration as an integral event in plant metabolism intensified during immune response. Using potato-avr/vr Phytophthora infestans systems and immunoassays we documented that potato immunity is accompanied by two waves of boosted ONOO¯ formation affecting guanine nucleotides embedded in RNA/mRNA and protein tyrosine residues. The early ONOO¯ generation was orchestrated with an elevated level of protein nitration and a huge accumulation of 8-nitroguanine (8-NO2-G) in RNA and mRNA pools confirmed as a biomarker of nucleic acid nitration. Importantly, potato cells lacking ONOO¯ due to scavenger treatment and attacked by the avr pathogen exhibited a low level of 8-NO2-G in the mRNA pool correlated with reduced symptoms of programmed cell death (PCD). The second burst of ONOO¯ coincided both with an enhanced level of tyrosine-nitrated proteins identified as subtilisine-like proteases and diminished protease activity in cells surrounding the PCD zone. Nitration of both RNA/mRNA and proteins via NO/ONOO¯ may constitute a new metabolic switch in redox regulation of PCD, potentially limiting its range in potato immunity to avr P. infestans.